Primary neuroendocrine tumor of liver-a rare case report - B., Mohan Babu; Laishram, Natasha; Laishram Purnima Devi,; Longjam, Sarmila; Singh, Ngairangbam Phalguni; Tampakmayum, Farhana (International Journal of Research in Medical Sciences, 2025)
The primary neuroendocrine tumor of the liver (PNET) is an exceptionally rare diagnosis, representing only 0.3% of all neuroendocrine tumors (NET). Due to its infrequency, accurate differentiation from other hepatic masses and exclusion of occult primary NETs are imperative. Establishing a definitive diagnosis of liver PNET often requires a comprehensive follow-up to rule out alternative primary causes. The liver is a frequent site for neuroendocrine metastases, and notably, primary neuroendocrine liver tumors typically demonstrate a more favorable prognosis compared to hepatocellular carcinoma and other malignant hepatic lesions. This paper reports on the case of a 74-year-old female patient who presented with pain in the right upper quadrant of the abdomen for two months. Following a triphasic CT scan and liver mass biopsy, the diagnosis of PNET was confirmed based on biopsy reports and immunohistochemistry (IHC). The patient underwent multimodality treatment; however, further intervention was deferred due to the patient's poor general condition. Instead, the patient was placed on the best supportive care.